A CHRONOSTRATIGRAPHY OF MID AND LATE-HOLOCENE SLOPE EVOLUTION: CREAGAN A’ CHAORAINN, NORTHERN HIGHLANDS, SCOTLAND - Reid E.; Thomas M.F. (My University, 2006)
Unusual exposure of the drift stratigraphy of a typical, vegetated hillslope in the Northern Highlands of Scotland has allowed reconstruction of its Holocene history. Graphic logging of palaeogully fill, sediment analysis, radiocarbon dating and microscopic investigation of horizon boundaries, link periodic slope instability to changes in hydrology and vegetation cover. The oldest preserved organic matter dates from about 7.5 cal. ka BP. Several millennia of subsequent stability were followed, at about 4.3 cal. ka BP, by destabilization whose magnitude and frequency markedly increased after about 2.7 cal. ka BP. Precipitation-driven weathering and erosion offer the best explanation for late-Holocene slope rejuvenation at this site, with change effected through long-lasting shifts in system equilibria as well as high magnitude inputs. Anthropogenic impacts on slope stability are apparently restricted to the last few hundred years. The timing and episodicity of slope evolution suggests climate forcing. Results raise the question of whether the extent of past and potential climate-driven Holocene slope evolution in non-glaciated uplands have been underestimated.
Keywords: SLOPE EVOLUTION; SCOTLAND; NW EUROPE; HOLOCENE CLIMATE CHANGE; DEBRIS FLOWS; COLLUVIUM; PEAT; PALAEOPODZOLS; WEATHERING RATES; Holocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен